Diversity and multiculturalism of LIS education. Issue 1 (27th December 2016) - Aytac, Selenay; Ma, Lai; Potnis, Devendra; Rorissa, Abebe; Chen, Hsin Liang; Hu, Xiao
ABSTRACT: The purpose of the panel is to raise the common questions about diversity and multiculturalism training in library schools, and engage the audience in a meaningful discussion about diversity and multiculturalism. We will discuss the importance of diversity and multiculturalism training in library and information science curricula by examining multiple countries/regions as case studies. We would be seeking answers to two major questions: "What do responsible library science educators need to do to educate librarians on diversity/multiculturalism/internationalism?" and "How can we educate future librarians so that they will have a greater perspective on diversity and multiculturalism?"